(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Vijay Tendulkar (1928-2008) is the master of ‘The Theatre of Cruelty’ in the Marathi Theatre and also known as ‘the Champion of Social Justice.’ He is one the earliest playwrights of Indian languages who has transformed the regional theatre into national theatre. Like Mohan Rakesh in Hindi, Badal Sarkar in Bangoli language, Vijay Tendulkar in Marathi Language, transformed the traditional Marathi theatre into modern naturalistic theatre and adopted certain trends of western drama in his plays. After the independence of India, Tendulkar is one of the leading figures of the theatre of protest in Marathi Language. His plays deal with the problems of Indian society. He uses the stage for the reformation in the attitude of the people. Women who have been given the secondary status in the society from the beginning of the civilization always remain in the centre of his play. Most of his plays are centered on problems of middle class society particularly women, downtrodden. He depicts the scenes and situations happening in the social and cultural life of India.